Diagnostic Value of Brain Tumor Neuroendoscopic Biopsy and Correlation with Open Tumor Resection - Chrastina, Jan; Novak, Zdenek; Riha, Ivo; Hermanova, Marketa; Feitova, Vera (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background The risks of stereotactic biopsy are increased not only in tumors located in the vicinity of vascular structures, but also in cystic, intraventricular, and periventricular lesions. The use of neuroendoscopy for cystic, intraventricular, or periventricular brain tumors is particularly advantageous because of the possibility of biopsy and immediate hemostasis under direct vision. Neuroendoscopy provides the possibility of controlling tumor-associated obstructive hydrocephalus by means of endoscopic third ventriculostomy or septostomy. The literature gives good evidence for the diagnostic benefits of neuroendoscopic biopsy. The correlation of the histology obtained by neuroendoscopic biopsy and subsequent surgical resection may allow the evaluation of the validity of diagnostic neuroendoscopic biopsy.Materials and Methods Between 2003 and 2010, 23 patients with suspected cystic brain tumor (12 males; age range, 21–75 years; mean age, 49.7 years; and 11 females; age range, 22–76 years; mean age, 59.1 years) and 35 patients with intraventricular or periventricular brain tumors (19 males; age range, 6–80 years; mean age, 43.9 years; and 16 females; age range, 11–78 years; mean age, 46.2 years) underwent navigated neuroendoscopic biopsy.Results Diagnostic samples were obtained in all cystic tumors and in 94.7% of intraventricular or periventricular tumors. Tumor resection after neuroendoscopic biopsy was performed in seven patients with cystic tumors. The results of the histological analysis of samples taken during endoscopic biopsy and surgical resection were identical in five of these patients (70.1%). Four patients with intraventricular or periventricular tumors underwent tumor resection after neuroendoscopic biopsy. The histological results of neuroendoscopic biopsy and tumor resection were identical in three patients (75%). Neuroendoscopic biopsy was performed in six patients with expansive pseudocyst after tumor resection and oncological therapy. The results of the neuroendoscopic biopsy matched the results of open surgery in four patients (66%). In the two remaining patients, there was a difference in tumor grading.Conclusion The diagnostic accuracy of neuroendoscopic biopsy samples can be compared with the results of stereotactic biopsy. The histological results of endoscopically taken biopsy samples and the final histological results obtained during open surgery correlate in the majority of patients, and underlines the high diagnostic validity of neuroendoscopic biopsy.
Keywords: endoscopy; intracranial tumor; intraventricular tumor